Policy Support On Walkability In Malang City - Winansiha, Erna; Antariksa, Antariksa; Surjono, Surjono; Setyoleksono, Amin (Fakultas Teknik, Universitas Brawijaya, 2015)
Walkability refers to how the pedestrians are facilitated and regarded as the users of the street (mode of transportation due to the public transportation walkability strategy). Malang plays a significant role as the second largest city in East Java Province. The Malang city shows some street problems recently. One of them is the lack of infrastructures for pedestrians. The congestion seems to be greater every year and lead to jaywalking pedestrians. The street activities show the motorized vehicles a lot. It seems that the pedestrians are being neglected. One of the components of walkability is the policy support to guarantee the pedestrians rights as the users of the street corridor.The study is aimed to analyze the walkability policy support. The existences of the policies and how they are implemented is the matter of the study. The component shows the degree of policy supports in order to respect the pedestrians. The collected data about the policies from national to local levels are evaluated using content analysis method. Among some policies, there are the presences of the related policies in national and local level. The number 79 of Government Regulation in 2013 about Traffic Network and Road Transport regulates the facilitation of the pedestrians in extension of the number 22 of Traffic Network and Road Tranport Act in 2009. At local level the pedestrians consideration is regulated by Local Regulation, number 4, in 2011 about the Malang City Master Plan 2010-2030. The quality of the policy support is still poor due to the pedestrians needs compared with the motorized ones. The presence of the number 03/PRT/M/2014 of Ministry of Public Work Regulation about The Guidance of Pedestrians Network Infrastructure Planning, Providing and Using in Urban Areas is specially designed in order to fulfill the pedestrians needs. This regulation respects the walking activity and facilitate pedestrians in a manner of convenience, safety and security. Because of the recently existence as the regulation so that the implementation has not done yet. But learning from some cases about street-traffic that had happened recently in Malang city, it can reflect the ignorance of the walking activities as the mode of transportation in accordance with improved public transportation. It recommends to revise City Master Plan of Malang which has the better planning of pedestrian facilities as an integration of transport network planning. There is an interesting finding about how much the act and regulation pay attention to the pedestrian needs. It shows an extreme leap that need to be examined on other next research.Keywords: walkability, pedestrian rights, policy support